Experimentation with Alcohol among Brazilian Adolescents According to the National School Health Survey (Universitas Medica, 2024)
Introduction: Experimentation with alcoholic beverages by young Brazilians, in addition to harming brain development, also interferes with psychological aspects, interfering with their quality of life and harming their academic development. Objective: To evaluate alcohol experimentation and associated factors among Brazilian adolescents. Method: This is a cross-sectional study, conducted by the National School Health Survey in 2019, with a sample of 159,245 Brazilian adolescents. Prevalence ratios were adjusted between the alcohol experimentation variable and risk factors, estimated by hierarchical multiple Poisson regression models in blocks with robust variance, weighted by sample weights. Results: The weighted adjusted prevalence of alcohol experimentation and 95% confidence interval for alcohol experimentation was 63.45% (95%CI: 62.88–64.02). Prevalence ratios adjusted for sociodemographic, family, mental health, behavior, and lifestyle variables all showed an association with alcohol experimentation. The variables behavior and lifestyle habits presented the highest prevalence ratios for experimentation with illicit drugs (1.25) and sexual intercourse (1.50) and remained associated in the final model, most of the factors in the blocks considered, with statistical significance (p < 0.001). Conclusions: The prevalence among Brazilian adolescents was high and associated with the study's risk factors. The occurrence of this phenomenon, which interferes with the physical and mental development of adolescents, requires new directions in public policies.